2014
DOI: 10.1111/jep.12196
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right journal for your systematic review

Abstract: The majority of the journals do not mention the acceptance of SRs in the instructions for authors section. Only a few journals require that SRs meet specific reporting guidelines, making interpretation of their findings across studies challenging. There is no correlation between the impact factor of the journal and its acceptance of SRs for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A further seven remarked on journal selection as part of a wider discussion of publishing 17 – 19 , 21 , 24 , 31 , 33 . Three articles were intended to be of interest to only specific audiences: psychiatrists 25 , the authors of systematic reviews 27 or anaesthetists 37 .…”
Section: Resultsmentioning
confidence: 99%
“…A further seven remarked on journal selection as part of a wider discussion of publishing 17 – 19 , 21 , 24 , 31 , 33 . Three articles were intended to be of interest to only specific audiences: psychiatrists 25 , the authors of systematic reviews 27 or anaesthetists 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Some journals accept only certain types of articles (e.g. systematic reviews), which must be considered by authors (Betini et al , 2014). Bavdekar and Save (2015) suggest that selection of a target journal should occur before the manuscript is even prepared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A range of guidelines has been established for systematic reviews, including the procedural handbook of the Cochrane Collaboration [5]; risk of bias tools, such as ROBIS [6]; reporting guidelines, as in the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) [7]; and guidance for making recommendations, such as Grading of Recommendations Assessment, Development and Evaluation [8]. Prominent journals issue specific instructions for authors of systematic reviews, typically requiring adherence to PRISMA, although one analysis found that this was explicitly demanded by merely 27% of journals publishing systematic reviews [9].…”
Section: Introductionmentioning
confidence: 99%